Clinical Audit to Optimize Pre-Endoscopy Checklist in Patients Undergoing GI Endoscopy - Zaeem Ahmad; Wardah Mohsin; Athar Pervez; Maheen Anwaar; Zuna Israr; Saniah Israr; Yumma Ali; Saba Mohsin; Muhammad Ahsan Farooq (Pakistan Journal of Gastroenterology, 2026)
Gastrointestinal (GI) endoscopy (both upper and lower) is an important diagnostic and therapeutic procedure. They are utilized in various diagnostic and therapeutic (both emergency and elective) procedures[1]. Concerns over patient safety and quality of care have grown in parallel with the increasing complexity of GI procedures[1, 2]. Endoscopy safety checklists serve as quality assurance tools to ensure systematic preparation, enhance procedure precision, and reduce risks[3]. Despite their importance, the use of these checklists varies across institutions, especially in low-resource settings. An increasing amount of research indicates that endoscopic safety checklists can reduce patient morbidity and mortality by preventing errors. As a result, endoscopic checklists are required for every treatment[4].